2000
DOI: 10.1017/s1357729800054825
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight responses to shearing ewes in early to mid gestation

Abstract: This study compared the effect on foetal growth of shearing ewes in very early pregnancy (day 50) with the effect of shearing later in pregnancy (day 70 or 100). One hundred and sixty ewes were allocated at day 49 of pregnancy to four ‘time of shearing’ treatments — pregnancy day 50 (P50), P70, P100 (no. = 45 ewes per treatment) and unshorn (shearing of this group occurred 43 days after weaning) (no. = 25); two methods of shearing (by standard comb and cover comb); and two levels (1 or 2) of pregnancy/rearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
2
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 13 publications
5
24
2
5
Order By: Relevance
“…Shearing pregnant ewes has consistently been reported to increase lamb birthweight, particularly if conducted during early to mid-gestation ( Figure S3). Associated with this response are increases in maternal feed intake, gestation length and maternal plasma glucose concentrations (Symonds et al 1988;Morris et al 2000;Keady and Hanrahan 2009;Banchero et al 2010). Although shearing is associated with a robust stress response in the ewe, these data suggest that its primary effect on birthweight is through increased feed intake, and hence nutrition of the developing lamb.…”
Section: Animal Behaviour and Welfarementioning
confidence: 95%
“…Shearing pregnant ewes has consistently been reported to increase lamb birthweight, particularly if conducted during early to mid-gestation ( Figure S3). Associated with this response are increases in maternal feed intake, gestation length and maternal plasma glucose concentrations (Symonds et al 1988;Morris et al 2000;Keady and Hanrahan 2009;Banchero et al 2010). Although shearing is associated with a robust stress response in the ewe, these data suggest that its primary effect on birthweight is through increased feed intake, and hence nutrition of the developing lamb.…”
Section: Animal Behaviour and Welfarementioning
confidence: 95%
“…On the other hand, cold stress in ewes (Hocquette et al, 1992) ram lambs (Ekpe and Christopherson, 2000; Doubek et al, 2003) and shearing (Morris et al, 2000;Merchant and Riach, 2002) induced increases in blood TH levels. The seasonal pattern of blood TH levels often showed maximal values during winter (cold months) and minimal during summer (hot months) (Salem et al, 1991;Webster et al, 1991;Okab et al, 1993;Menegatos et al, 2006).…”
Section: Season Effectsmentioning
confidence: 99%
“…A similar relationship was observed by Revell et al (2000) who suggested the reduction may reflect an increase in the expression of the IGF-I receptor. The IGF-I receptor is regulated, in part, by thyroid hormones, which, in mid pregnancy shorn ewes, display a period of elevation for up to several weeks (Morris et al 2000). However, under conditions in which mid pregnancy shearing tended to increase twin-lamb birth weight, neither short-or long-term elevation of maternal thyroid hormones had any effect (Kenyon et al 2005).…”
Section: Discussionmentioning
confidence: 99%